Research on the production of high-purity calcium lactate from poultry eggshells and their application in food - Phan Thanh Tam; Nguyen Hai Van; Nguyen Ngoc Hieu (Vietnam Journal of Science, Technology and Engineering)
Poultry eggshells waste is a the environmental concerns. Transforming biowaste into value-added products is one of the promising green solutions. Converting eggshell calcium carbonate into organic calcium is a promising strategy to treat this waste. The aims of this study is to produce high-purity lactate from poultry eggshells waste and to apply this preparation in food. Calcium sourced from poultry eggshells, recovered from food production facilities, has been thoroughly treated to remove membranes. The calcium was then extracted with lactic acid to produce high-purity organic calcium. The extraction process parameters were optimised: the ratio of eggshell to 16% lactic acid solution was 1:12 (w/v), reaction temperature 35℃, crystallisation at 25oBx, and drying at 80℃ for 6 hours. This process yielded a calcium lactate product with a purity exceeding 99%, and a recovery efficiency surpassing 90%, meeting the quality criteria outlined in Vietnamese standard QCVN 4-13:2010/BYT. Additionally, 0.2% (126 mg Ca/330 ml) of this calcium product was successfully incorporated into passion fruit juice, providing a high-quality product with potential to supplement organic calcium in human diets.